Study on the Basic Characteristics of the Geothermal Temperature Field in the Middle and Deep Layers of the Liaohe Depression - Lin, Zhongkuo; Liu, Yong; Zhou, Hong; Zheng, Yuming (Transactions on Environment, Energy and Earth Sciences, 2024)
The Liaohe Depression is a large "thermal field" with a Moho depth of 33 kilometers. It is located in a regional mantle uplift zone, where the crust is relatively thin, providing favorable conditions for the upward transfer of mantle heat. The characteristics of the geothermal temperature field in the middle and deep layers of the Liaohe Depression are not only controlled by the basic regional geological and geothermal features but are also influenced by several key factors. These include the burial depth of the bedrock, the lithology and structure of the bedrock and overlying unconsolidated layers, groundwater activity, magmatic activity, fault activity, and local variations in the content of radioactive elements. These factors, to varying degrees, affect the distribution of the temperature field. The regional fault structures are well-developed, and the bedrock shows significant fluctuations. This unique geological structure makes bedrock burial a regionally significant factor in controlling the geothermal temperature. According to the basic principles of heat conduction, the heat from deep sources is distributed among the geological bodies, forming the current basic characteristics of the temperature field in the Liaohe Depression. Through the study of these factors and the temperature field patterns, more accurate geothermal predictions can be made, laying a solid foundation for the development of geothermal exploitation plans.